Etanolic extract of Ling Zhi Mushroom (Ganoderma lucidum) improves lipid profile, CRP and histopathological of liver in dislipidemia model rats - Soegianto, Jap Yulius Billy; Samodro, Pugud; Wisesa, Sindhu; Hernayanti, Hernayanti; Setyono, Joko; Arjadi, Fitranto (Biogenesis: Jurnal Ilmiah Biologi, 2023)
.